2021
DOI: 10.3390/en14030726
|View full text |Cite
|
Sign up to set email alerts
|

Some Aspects of the Modelling of Thin-Layer Drying of Sawdust

Abstract: Drying of spruce, beech, willow, and alder sawdust was examined in a laboratory type dryer. The effect of drying air temperature T (25, 60, and 80 °C) and airflow velocity v (0.01, 0.15, and 1.5 m/s) was investigated. The obtained results demonstrated that drying air temperature and airflow velocity have impacts on the drying of sawdust. The experimental dehydration data of sawdust obtained were fitted to theoretical, semi-theoretical, and empirical thin-layer models. The accuracies of the models were estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 81 publications
(95 reference statements)
0
5
0
Order By: Relevance
“…Drying temperature plays an important role in the drying process. It can be observed that the higher the air temperature, the shorter the drying time and the higher the drying rate.The fastest reduction in moisture content was obtained at a temperature of 90 o C and an air velocity of 3 m/s which took 330 minutes.Meanwhile, the longest time to reach a final moisture content of 19% was at a temperature of 70 o C and an air velocity of 2 m/s with a time of 550 minutes.A decrease in drying time and an increase in drying rate with increasing drying temperature have been observed for sawdust of spruce, beech, willow, alder [9]. and drying of poplar wood particles [10].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Drying temperature plays an important role in the drying process. It can be observed that the higher the air temperature, the shorter the drying time and the higher the drying rate.The fastest reduction in moisture content was obtained at a temperature of 90 o C and an air velocity of 3 m/s which took 330 minutes.Meanwhile, the longest time to reach a final moisture content of 19% was at a temperature of 70 o C and an air velocity of 2 m/s with a time of 550 minutes.A decrease in drying time and an increase in drying rate with increasing drying temperature have been observed for sawdust of spruce, beech, willow, alder [9]. and drying of poplar wood particles [10].…”
Section: Resultsmentioning
confidence: 99%
“…There are few papers related to mathematical modelling of wood drying. Brys et al Drying spruce, beech, willow, and alder sawdust, higher drying air temperatures and air flow velocity result in lower drying times and higher drying rates [9]. Hosseinabadi et al the effective moisture diffusivity and activation energy of poplar wood particles increases due to increases in temperature and air velocity [10].…”
Section: Introductionmentioning
confidence: 99%
“…Thin-layer drying is the term used for the lumped systems [10]; that is to say, a uniform temperature is generally assumed because of the thin structure of the fruit or vegetable that has been sliced before drying. Although the thin-layer models are classified as theoretical, semi-empirical (semi-theoretical) and empirical [10], the empirical equations are still widely used because of their simplicity and ease of computation [11,12]. Parameters of theoretical models have physical meaning because they are based on the general theory of heat and mass transfer laws, and they take into account the fundamentals of the drying process.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, these models can be used to explain the phenomena occurring during drying. Nevertheless, they are more difficult to apply compared to semi-empirical and empirical models [12,13]. The semi-empirical models are derived from Fick's second law of diffusion (theoretical model) or Newton's law of cooking i.e., a simplified version of Fick's second…”
Section: Introductionmentioning
confidence: 99%
“…The models and curves of TLD and convective dryers have been used to study the drying kinetics of food materials (Wang and Singh 1978;Vega et al 2007;Kumar et al 2012), agricultural products (Lee and Kim 2009;Kaleta et al 2013;Kaur andSingh 2014), lignocellulosic biomass (Zarea Hosseinabadi et al 2012;Arabi et al 2017;Brys et al 2021), and sugarcane bagasse (Freire et al 2001;Vijayaraj and Saravanan 2007;Shah and Joshi 2010). However, the effect of halogen rays has not yet been studied on bagasse particle drying kinetics.…”
Section: Introductionmentioning
confidence: 99%